2019
DOI: 10.1002/jcp.28252
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines in bladder cancer

Abstract: The presence of inflammatory cells and their products in the tumor microenvironment plays a crucial role in the pathogenesis of a tumor. Releasing the cytokines from a host in response to infection and inflammation can inhibit tumor growth and progression. However, tumor cells can also respond to the host cytokines with increasing the growth/invasion/metastasis. Bladder cancer (BC) is one of the most common cancers in the world. The microenvironment of a bladder tumor has been indicated to be rich in growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 129 publications
1
15
0
1
Order By: Relevance
“…Several studies have indicated that the inflammatory status and immune cell infiltration promote the initiation of cancer cells, which inspired us to detect the potency of IFRGs with distinguished expression in various clinicopathologic states [24,25]. Some previous studies that discovered the differential genes in BCa and non-BCa patients also provided insight into the detection at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the inflammatory status and immune cell infiltration promote the initiation of cancer cells, which inspired us to detect the potency of IFRGs with distinguished expression in various clinicopathologic states [24,25]. Some previous studies that discovered the differential genes in BCa and non-BCa patients also provided insight into the detection at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…Progression was seen in 38.1% of DM patients and 28.2% of non-DM patients. Evidence suggests that the hallmark of cancer evolution in DM patients is chronic inflammation caused by insulin, insulin-like growth factor-1, proinflammatory cytokines, oxidative stress and growth factor effects [46]. In particular, low-grade systemic inflammation, characteristic of type 2 DM, could favor initiation and progression of bladder cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory cells produce growth factors and cytokines that activate downstream nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), activator protein-1, signal transducer and activator of transcription (STAT) and mothers against decapentaplegic (SMAD) transcription factors, and caspase proteins to produce tumour-promoting factors that induce cell proliferation and survival factor production, which promotes the development of tumours and the growth and survival of tumour cells. 19 …”
Section: Inflammation and Tumour Developmentmentioning
confidence: 99%
“…18 Inflammatory cells produce growth factors and cytokines that activate downstream nuclear factor kappa-light-chainenhancer of activated B cells (NF-jB), activator protein-1, signal transducer and activator of transcription (STAT) and mothers against decapentaplegic (SMAD) transcription factors, and caspase proteins to produce tumour-promoting factors that induce cell proliferation and survival factor production, which promotes the development of tumours and the growth and survival of tumour cells. 19 Tumour induction is the process by which a single tumour cell grows into a fully developed primary tumour. The growth of the initial cells depends on both the promotion of cell proliferation and the reduction of cell death, both of which can be stimulated by inflammation.…”
Section: Inflammation and Tumour Promotionmentioning
confidence: 99%